Fertilizing lychee plants with phosphorus at time of planting in Brazil - Prado, Renato de Mello [UNESP]; Gondim, Ancélio Ricardo de Oliveira [UNESP]; Correia, Marcus André Ribeiro [UNESP] (Hindawi, 2012)
The objective of this research was to study the effects of P fertilizers applied at time of planting on lychees' nutritional status and on plant growth. The treatments consisted of five doses of P: zero, 50, 100, 200, and 300 g of P2O5 per plant, furnished by triple superphosphate. Plant diameter was evaluated during two years and the plants' nutritional status on the second year. The second year foliar levels of macro and micronutrients (with the exception of Zn) were increased by the P fertilizer. The orchard's initial development, especially during the second year, was also influenced by the fertilizer. The P doses of 164 and 158 g of P2O5 per plant resulted in the largest plant diameter after the first and the second year, respectively. These doses were found to be associated with a foliar P level of <1.4 g kg-1. © 2012 Renato de Mello Prado et al.
Keywords: Litchi chinensis